The Issues And Challenges Facing The Female Entrepreneurs In Lagos State, Nigeria - Hauwa , Daniyan-Bagudu; Mohd Khan, Shazida Jan; Roslan, Abdul-Hakim (2016)
This study investigates on the challenges and issues that female entrepreneurs faced in developing counties like Nigeria. From the 80 observations descriptive statistics was employed. The outcome of the findings indicates that the success of female entrepreneurs is hindered by family pressures, unexposed to market, their lack of education and discrimination against their male counterparts. The study recommends that mentorship programs that will enlighten the female entrepreneurs must be put in place and the government should offer financial support to the female entrepreneurs to assist them in boosting their business.